Aplikasi Android “Taksiran Berat Janin” (Si-RAJA) Penolong Bidan dalam Memantau Pertumbuhan Janin - Darwitri Darwitri; Respatiningrum Respatiningrum; Metasari Sihaloho; Utami Dewi (LPPM Hang Tuah Pekanbaru, 2023)
Estimated Fetal Weight is one way to monitor the growth of the fetus in the womb. Along with the development of technology, the use of Android can be used as a medium for health educational information. The purpose of this study was to analyze the effect of using the Fetal Weight Estimation Android Application (Si-RAJA) on the knowledge of midwives in monitoring fetal growth. This study used a quasi-experimental method with one group pre-test-post-test design for 30 midwives who were taken using a proportionate stratified random sampling technique. Data were collected from September to October 2021 at Puskesmas throughout Tanjungpinang City. Data analysis used dependent samples t-test. The results showed that the mean knowledge of the estimated fetal weight increased from 69 (Pre-Test) to 78 (Post-Test). There is a significant difference in knowledge before and after using the Si-RAJA android application with a p-value of 0.000. Midwives show satisfaction with the use of the Si-RAJA application and the Si-RAJA application can also increase the knowledge of midwives in monitoring fetal growth.